Monte-Carlo Simulations Revised: A Reply to Arqus - Sabrina Dorn (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2009)
This contribution revises Monte-Carlo based simulation techniques as used in BusinessTaxation and Accounting literature, most prominently proposed by fellows ofTherefore, we focus on a methodically orientated discussion. Our results suggestthe standard approach leads to biased estimates of expected discounted tax paymentsassuming cash flow uncertainty and incomplete loss-offset regulations. We built upcritique by giving an analytical expression for expected discounted tax paymentsformulating the structure of probability weighted tax states in the future conditionalcash flows above or be-low zero. Consequently, this enables us to evaluate the resultsobtained from the standard Monte-Carlo approach within a numerical analysis.
Keywords: G31; H25; K34; 330; Arqus; cash flow uncertainty; limited loss-offset; Monte-Carlo simulations